Jamaican economy : review and outlook. - Vanriel, Wesley (1992)
Reviews Jamaica's economic policies and performance in 1991, including the liberalization of the foreign exchange trading system. Points out that the stabilization of the exchange rate and the control of inflation are the major challenges facing the country.